Evaluating the effectiveness of translation technology training in Iran: A perception-based mixed methods study - Akhlaghi Ilkhchi, Amirreza; Monsefi, Roya; Yalsharzeh, Reza; Taghavi, Morteza (Cadernos de Tradução, 2025)
Although evaluating the effectiveness of training courses on translation technology is essential, previous studies have primarily evaluated such courses based on trainee translators’ satisfaction or knowledge acquisition, paying little attention to behavioral changes in trainee translators and the long-term outcomes of the training. Drawing on convergent mixed methods design, this study aimed to evaluate the effectiveness of the translation technology course provided by Iranian universities at MA level based on the perceptions of Iranian MA translation students and graduates. To this end, both quantitative and qualitative data were collected from 63 Iranian MA translation students and graduates via two questionnaires. The results, according to the New World Kirkpatrick Model, indicated that the translation technology course provided by Iranian universities at MA level seems to lack training effectiveness. The findings suggest that there possibly exists a gap between what is taught and the needs of the translation market in the Iranian context.